Komparasi Ruang Domestik pada Rumah Tradisional di Desa Gubugklakah Malang dan Desa Sidatapa Buleleng - Gracella Renia Candrakirana; Ni Ketut Ayu Siwalatri; Antonius Karel Mukti Wibowo (Universitas Sebelas Maret Surakarta, 2024)
The cultural diversity of Indonesia affects the spatial layout and functioning of spaces in residential areas because domestic spaces, which are a room of basic residential activities, are formed from the activities of residents and local beliefs. This research aims to compare domestic spaces in the traditional houses of Gubugklakah Village, Malang, and Sidatapa Village, Buleleng, using comparative qualitative methods through observations, interviews, and documentation studies. The research results show differences where in Gubugklakah Village, the kitchen is positioned at the back of the building, emphasizing its function as a private working area for women. Meanwhile, in Sidatapa Village, the kitchen is placed in the middle of the building with attention to creating a different spatial hierarchy.